Biochemical changes in hybrid pumpkin seeds at different stages of maturation (Revista Ciência Agronômica, 2017)
This study aimed to evaluate biochemical changes in seeds of the pumpkin hybrid, ‘Jabras’, from fruit harvestedat different stages of maturation (15, 30, 45, 60 and 75 days after anthesis). Thirty fruit were harvested at each stage, withthe seeds from 15 of the fruit being extracted immediately. The remaining 15 were stored for twenty days in plastic boxesand the seeds extracted after this period. After processing and drying the seeds, the following were determined: moisturecontent, germination, first count and antioxidant enzyme activity (peroxidase, ascorbate peroxidase, catalase and superoxidedismutase). Seeds from the fruit harvested at 30 DAA displayed low values for germination and vigour and high antioxidantenzyme activity, indicating that they were immature and that drying possibly caused damage to the system of cell membranes.The results obtained in this study demonstrated that analysis related to changes in the activity of enzymes during developmentand maturation of the seeds was effective in evaluating the physiological and biochemical changes in pumpkin seeds of the‘Jabras’ cultivar.